2012
DOI: 10.4103/2229-5186.98685
|View full text |Cite
|
Sign up to set email alerts
|

Studies on inclusion complex as potential systems for enhancement of oral bioavailability of olmesartan medoxomil

Abstract: Background: Olmesartan medoxomil (OLM), an anti-hypertensive agent administered orally, has absolute bioavailability of only 26% due to the poor aqueous solubility (7.75 μg/ml). Inclusion complexation with cyclodextrins (CD) has been reported to increase the aqueous solubility of various compounds. Aim: The present investigation aimed to enhancing the oral bioavailability of OLM by inclusion complexation with 2-hydroxypropylβ-cyclodextrin (HP-β-CD). Materials and Methods: The inclusion complexes with HP-β-CD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Interactions can also be observed for the physical mixtures, even in the case of physical mixtures prepared without grinding, but only gentle mixing with a spatula, but they are weaker than those in the kneaded products. The interaction between OLM and 2 hydroxypropyl-β-CD even in the physical mixtures was also reported by Thakkar et al [35]. The smaller mass loss in the temperature range of 40-110 • C observed in the case of KP compared to PM and PMG proves a more intense interaction of OLM and RM-β-CD when the kneading method was used, since the driving force for complexation involves the replacement of high-energy water molecule in the host cavity by guest molecules [46].…”
Section: Thermal Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…Interactions can also be observed for the physical mixtures, even in the case of physical mixtures prepared without grinding, but only gentle mixing with a spatula, but they are weaker than those in the kneaded products. The interaction between OLM and 2 hydroxypropyl-β-CD even in the physical mixtures was also reported by Thakkar et al [35]. The smaller mass loss in the temperature range of 40-110 • C observed in the case of KP compared to PM and PMG proves a more intense interaction of OLM and RM-β-CD when the kneading method was used, since the driving force for complexation involves the replacement of high-energy water molecule in the host cavity by guest molecules [46].…”
Section: Thermal Analysissupporting
confidence: 78%
“…Complexation of active pharmaceutical ingredients with CD is one of the valuable strategies used to enhance the solubility of poorly water-soluble drugs, the dissolution rate, and consequently their bioavailability [28,34]. Thakkar et al [35] have investigated the inclusion of OLM in HP-β-CD cavity and reported significantly higher saturation solubility, dissolution rate, and intestinal permeation for OLM/HP-β-CD binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The unabsorbed drug may cause gastrointestinal side effects such as abdominal pain, dyspepsia, gastroenteritis, and nausea. [11] In the literature nanoparticles, [12] nanosuspension [10] and complexation with cyclodextrin [11] have been reported to improve solubility of OLM. Therefore, formulation approaches are being explored to enhance dissolution of OLM using poloxamer 407.…”
Section: Original Articlementioning
confidence: 99%
“…6,7 Several literature reports have demonstrated the application different solubility enhancement technologies for improving biopharmaceutical performance of the drug. [8][9][10][11][12] However, beyond solubility, many other rate-limiting factors tend to affect the oral bioavailability of OMT. Some of them are first-pass effect and terminal metabolism by gut enzymes.…”
Section: Introductionmentioning
confidence: 99%